(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper seeks to examine the presence of female artists, scientists, and politicians at the Vuk’s Fair, the cultural event held every September since 1933 in the village of Tršić, the birthplace of Vuk Stefanović Karadžić whose work and person have always been a strong mobilising factor in the social reality of the region. This is why I seek to examine how the stereotypes about gender relations are created and transferred through Vuk’s “victorious” cultural concept and language strongly based on oral traditions. In the interest of brevity, my paper will focus mostly on the women who took a notable part in the Vuk’s Fairs as either guest speakers or participants of the main closing ceremony. Since the very first Vuk’s Fair, the appearance of the guest speaker has always been considered the high point of this event. Over the course of the last 90 years, only four women have ever been given this coveted role. Even the women who spoke at the Vuk’s Fairs spoke about men: Tito, Vuk, Jovan Sterija Popović, and Ivo Andrić. The first woman to speak at the Vuk’s Fair was Mitra Mitrović, the minister of education, who spoke in 1947. The next female speaker came 47 years later when Nada Popović Perišić, the minister of culture, spoke in 1995. After her came the writer Vida Ognjenović in 2006, while Angela Richter, the first and only foreign guest speaker, spoke at the Fair in 2011. In sharp contrast to this lack of female guest speakers at the closing ceremony, most of the participants in the other events which take place during the Vuk’s Fair were women. Apparently, even though the main ceremony hasn’t been particularly open to female voices, women are welcome to appear at the Fair as long as they are providing entertainment. This is a very clear indication of the ever-growing tabloidization of women and their treatment of them as a commodity to be consumed. Taking all of this into account we can note that it seems that as a nation we are stuck between the outdated and shaky gender role assigned to men and the freedom these men grant women with the obligatory apology that other men should please, excuse their wives. Equally as shaken are our democratic tendencies, values, and reaches.